Embryo and Developmental Toxicity of Cefazolin Sodium Impurities in Zebrafish - Chen, Bo; Gao, Zhu-Qing; Liu, Ying; Zheng, Yang-Min; Han, Ying; Zhang, Jing-Pu; Hu, Chang-Qin (Frontiers in Pharmacology, 2017)
Cefazolin sodium is an essential drug that is widely used in clinical therapy for certain infective diseases caused by bacteria. As drug impurities are considered to be one of the most important causes of drug safety issues, we studied embryotoxicity, cardiotoxicity and neurotoxicity of nine cefazolin sodium impurities in zebrafish embryo and larvae for the objective control of impurity profiling. LC-MS/MS was employed to analyze the compound absorbance in vivo, and the structure-toxicity relationship was approached. Our results suggested that the structure of MMTD (2-mercapto-5-methyl-1, 3, 4-thiadiazole) is the main toxic functional group for embryo deformities; the 7-ACA (7-aminocephalosporanic acid) structure mainly affects motor nerve function; and both the MMTD and 7-ACA structures are responsible for cardiac effects. Impurity G (7-ACA) presented with the strongest toxicity; impurity A was most extensively absorbed to embryo and larvae ; and impurity F (MMTD) exhibited the strongest apparent toxic effect; Therefore, impurities F and G should be monitored from the cefazolin sodium preparations.